Pengembangan Aplikasi Pengenalan Budaya Kasepuhan Cirompang berbasis Virtual Reality untuk Pembelajaran IPAS di Sekolah Dasar - Ginanjar, Ajeng; Rahmani, Anggi; Adiputra, Dede Kurnia; Suwarno (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The Independent Curriculum is a curriculum with diverse intracurricular learning where the content will be more optimal so that students have enough time to explore concepts and strengthen competencies. The problem that occurred at SDN Jatimulya 1 was that teachers had difficulty choosing the right media in implementing the Independent Curriculum, so researchers analyzed the problems found to find the right solution. Through the initial research study, researchers also found problems in the learning of the